Methotrexate and sulfasalazine promote adenosine release by a mechanism that requires ecto-5'-nucleotidase-mediated conversion of adenine nucleotides. - Morabito, L (1998)
We and others have shown that an increased extracellular concentration of adenosine mediates the antiinflammatory effects of methotrexate and sulfasalazine both in vitro and in vivo, but the mechanism by which these drugs increase extracellular adenosine remains unclear. The results of the experiments reported here provide three distinct lines of evidence that adenosine results from the ecto-5'-nucleotidase- mediated conversion of adenine nucleotides to adenosine. First, pretreatment of a human microvascular endothelial cell line (HMEC-1) with methotrexate increases extracellular adenosine after exposure of the pretreated cells to activated neutrophils; the ecto-5'-nucleotidase inhibitor alpha, beta-methylene adenosine-5'-diphosphate (APCP) abrogates completely the increase in extracellular adenosine. Second, there is no methotrexate-mediated increase in extracellular adenosine concentration in the supernate of cells deficient in ecto-5'-nucleotidase, but there is a marked increase in extracellular adenosine concentration in the supernates of these cells after transfection and surface expression of the enzyme. Finally, as we have shown previously, adenosine mediates the antiinflammatory effects of methotrexate and sulfasalazine in the murine air pouch model of inflammation, and injection of APCP, the ecto-5'-nucleotidase inhibitor, abrogates completely the increase in adenosine and the decrement in inflammation in this in vivo model. These results not only show that ecto-5'-nucleotidase activity is a critical mediator of methotrexate- and sulfasalazine-induced antiinflammatory activity in vitro and in vivo but also indicate that adenine nucleotides, released from cells, are the source of extracellular adenosine.